Description of Farmer's Clean and Healthy Living Behavior in the Workplace Order - Alfid Tri Afandi; Nurfika Asmaningrum; Ayu Rahmawati; Marsya Nurrahmawati; R.A Arsyifa Nanda; Dani Saputra; Sonia Mila Dewi; Rizka Maulida; Firman Ramadhan; Mulenda Isdayana (Universitas Bondowoso, 2022)
Introduction: Clean and Healthy Living Behavior is one of the government programs that aims to encourage people to increase knowledge and apply healthier life behaviors in various workplace settings. This study aims to describe the clean and healthy living behavior of farmers in the workplace setting. Methods: This study uses an observational quantitative method with a descriptive-analytical research design and a cross-sectional study approach. The sampling technique used quota sampling with the number of samples that met the inclusion and exclusion criteria, namely 80 respondents. Collecting data using the Questionnaire for the Assessment of Clean and Healthy Life Behavior in the Workplace Arrangement from the Ministry of Health of the Republic of Indonesia. Results: The results showed that 44 farmers (55%) had a smoking habit while at work, 63 farmers (78.8%) did not consume or buy food sources from the workplace, and 44 farmers (55%) did not do a physical activity outside. working hours, 46 farmers (57.5%) did not wash their hands in running water, 69 farmers (87.5%) did not try to eradicate larvae at work, 52 farmers (65%) did not use clean water facilities, 62 farmers (77 .5%) perform defecation and defecation in healthy latrines/toilet, 67 farmers (83.8%) dispose of waste in its place, and 54 farmers (67.5%) have used the appropriate PPE. Conclusion: Clean and healthy living behavior needs to be done in a disciplined manner and there needs to be an evaluation that can be started from local health workers.